2000
DOI: 10.2169/internalmedicine.39.715
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Serum Hepatocyte Growth Factor for the Diagnosis of Amyloidosis.

Abstract: Objective The diagnosis of amyloidosis still relies on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In contrast, the serum VEGF levels in patients with amyloidosis were lower than those in patients without amyloidosis (0·06 ng/ml and 0·35 ng/ml respectively; P < 0·005). Recently, the usefulness of serum HGF for the diagnosis of amyloidosis has been reported by Shikano et al (2000). They demonstrated that the serum HGF levels in patients with amyloidosis were increased significantly compared with those of healthy volunteers (2·26 ng/ml vs. 0·2 ng/ml, P < 0·0001).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the serum VEGF levels in patients with amyloidosis were lower than those in patients without amyloidosis (0·06 ng/ml and 0·35 ng/ml respectively; P < 0·005). Recently, the usefulness of serum HGF for the diagnosis of amyloidosis has been reported by Shikano et al (2000). They demonstrated that the serum HGF levels in patients with amyloidosis were increased significantly compared with those of healthy volunteers (2·26 ng/ml vs. 0·2 ng/ml, P < 0·0001).…”
Section: Discussionmentioning
confidence: 99%
“…HGF is a pro-angiogenic cytokine activated by tissue-type plasminogen activator [26]. It has been reported in recent years that serum HGF level was significantly increased in patients with systemic amyloidosis (the serum HGF 0.39 ng/ml), but no significant differences were found between AL and AA amyloidosis, and the serum HGF level in patients with amyloidosis who died within one year of measurement was significantly higher than that in patients who lived for more than one year (2.83 ± 2.85 ng/ml versus 0.49 ± 0.26 ng/ml, P <0.01) [27]. Thus, the measurement of serum HGF level is considered to be a valuable predictor of the prognosis of amyloidosis patients [28].…”
Section: Discussionmentioning
confidence: 80%
“…However, these proteins are also implicated in other amyloidoses. For example, increased levels of HGF, which is controlled by HGFA, appear to be a good prognostic marker for various types of systemic amyloidosis 57 . An important question that arises is, for what reason the finger domain has evolved as a conserved amyloid-binding module and thus, in what physiological systems it may play its role.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the vitreous proteome showed that FXII and the contact system are upregulated in proliferative diabetic retinopathy 56 . A recent study showed that the activity of the enzyme carbonic anhydrase I is increased in the diabetic eye, leading to alkalinization of the vitreous 57 . For unknown reasons, this induces activation of FXII and the kallikrein-kinin system, explaining the pathologically increased vascular permeability.…”
Section: Involvement Of the Contact System In Diseasementioning
confidence: 99%
See 1 more Smart Citation